Study of the dietary and anthropometric profile and identification of determining factors in adolescents at school in the Khemisset region of Morocco - Yassine Bensaid; Aziz Akardalou; Soufiani Abdelaati; Abderezzak Khadmaoui (Roczniki Panstwowego Zakladu Higieny, 2023)
Background. The nutritional status and dietary diversity of adolescents play a crucial role in their growth, development, and overall health. Objective. The aim of this study is to assess the nutritional status and determine the dietary diversity score in urban and rural school settings among Moroccan adolescents. Material and Methods. We conducted a descriptive cross-sectional study in public schools in Khemisset in the municipality of Sidi Allal El Bahraoui, Morocco. We used a questionnaire to collect sociodemographic data and a 24- hour dietary recall to calculate the dietary diversity score. Results. This study included 215 students. The mean BMI was 21.06 ± 0.23 kg/m2, with 60.8% of students having a normal BMI, 24.5% being underweight, 11.8% overweight, and 2.8% obese. The mean dietary diversity score was 5.672±0.956, with 21% having a low dietary diversity score, 12% having a high score, and 67% having a moderate score. Factors associated with nutritional status were place of residence, type of delivery, and age, while the dietary diversity score was associated with school level and BMI of adolescents. Conclusion. The data from the study show that the diet of adolescents in the Khemisset region of Morocco is moderately diversified. In addition, the prevalence of underweight and overweight was worrying, underlining the need for multiple strategic interventions to improve the health status of adolescents.